Long term outcomes of intestinal rehabilitation in children with neonatal very short bowel syndrome: Parenteral nutrition or intestinal transplantation. Issue 2 (April 2019) - Norsa, Lorenzo; Artru, Solene; Lambe, Cecile; Talbotec, Cecile; Pigneur, Benedicte; Ruemmele, Frank; Colomb, Virginie; Capito, Carmen; Chardot, Christophe; Lacaille, Florence; Goulet, Olivier
Summary: Background & aims: Intestinal rehabilitation is the preferred treatment for children with short bowel syndrome (SBS) whatever the residual bowel length, and depends on the accurate management of long-term parenteral nutrition (PN). If nutritional failure develops, intestinal transplantation (ITx) should be discussed and may be life-saving. This study aimed to evaluate survival, PN dependency and nutritional status in children with neonatal very SBS on PN or after ITx, in order to define indications and timing of both treatments. Patients and methods: This retrospective cross-sectional study enrolled 36 children with very SBS (<40 cm) who entered our intestinal rehabilitation program from 1987 to 2007. Results: All the children on long-term PN ( n  = 16) survived with a follow-up of 17 years (9–20). Six of them were eventually weaned off PN. Twenty children underwent ITx: eight children died (40%) 29 months (0–127) after Tx. The others 12 patients were weaned off PN 73 days (13–330) after Tx. Follow-up after transplantation was 14 years (6–28). Seven out of 8 (88%) patients with a history of gastroschisis required ITx. Patients who required ITx had longer stoma duration. Conclusion: Survival rate of children with very short bowel was excellent if no life-threatening complications requiring transplantation developed. Gastroschisis and delayed ostomy closure are confirmed as risk factor for nutritional failure. Intestinal rehabilitation may allow a total weaning of PN before adulthood. A follow-up by a multidisciplinary team is necessary to avoid PN complications in order to minimize indications for ITx. Highlights: Multiple catheter sepsis and thrombosis are risk factors for the need of intestinal transplantation. Patients with gastroschisis or longer duration of stoma evolves more frequently to intestinal transplantation. The survival rate of children with neonatal very short bowel syndrome is 68%: all deaths occurred after intestinal transplantation. One third of patients on long term parenteral nutrition can be weaned. The objective of intestinal rehabilitation should be to avoid nutritional failure requiring intestinal transplantation.